Inhibition of gingival fibroblast growth by Bacteroides gingivalis. - Larjava, H (1987)
Human gingival fibroblasts were exposed in culture to cell extracts of different black-pigmented Bacteroides species, and their growth was monitored by determining thymidine uptake and counting cells. Of the Bacteroides species tested (B. gingivalis, B. asaccharolyticus, and B. intermedius), B. gingivalis gave the extract with the strongest inhibitory effect on fibroblast thymidine uptake. Linear inhibition reaching 80% of the control level was obtained with a dose of 100 micrograms of B. gingivalis extract protein per ml. The effect of B. asaccharolyticus resembled that of B. gingivalis, but even at the highest dose tested B. intermedius had only a slight inhibitory effect. When fibroblasts were counted after 2- and 4-day exposures to B. gingivalis extracts, a clear depression in the number of fibroblasts was found. The effects of extracts obtained from early and late growth phases of B. gingivalis cultures were similar. A fraction of B. gingivalis consisting essentially of lipopolysaccharides (LPSs) was obtained by degrading the extract proteins with proteinase K. Silver staining of polyacrylamide gels revealed a LPS pattern with a molecular mass ranging from 37 to 60 kilodaltons. This LPS-rich fraction caused inhibition of thymidine uptake by gingival fibroblasts similar to that caused by the native extract alone. Thus, the inhibition of gingival fibroblast growth by B. gingivalis appeared to be LPS mediated. This inhibitory effect of B. gingivalis on oral fibroblast growth may be a virulence factor of this bacterium.